Pemberdayaan Desa Wisata Melalui Pengembangan Wisata Air Terjun Songgo Tuyo di Desa Nogosari Kec. Pacet Kabupaten Mojokerto - Imam Safii; Alfin Fatih; Ashad Abdillah Rosyid; M Afif Zamroni; Hasyim Asy'ari (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
Natural tourism assets are frequently driven by market forces where rich people make investment by collaborating with local government. It is rarely that the local community has the authorization to manage the assets by themselves, including the people in Nogosari village with its Songgo Tuyo waterfalls. This community service aimed at supporting and assisting the local people to optimize the available assets by themselves. Asset Based Approach (ABA) was employed by maximizing the promotion of the existing assets through the combination of online promotion and a photo competition in the tourism area. The programs was succesful in raising new enthusiasm from the community to develop the tourism resources not only the waterfalls but also the infrastructure, services, cultural, culinary, and merchandise, and attracted more tourists to come